Safety, Health and Environmental Auditing : a Practical Guide, Second Edition. - Pain, Simon Watson (CRC Press, 2018)
"This new edition builds on the success of the first edition. It has been enhanced to embrace new topics including Due Dilgence, EHS Auditing, Process Safety Auditing, and a chapter summarizing auditing with the relevant ISO standards. The rest of the book has been updated to fit with the guidance and requirements set out with the changes in the ISO standards. The goal of this book remains the same, to provide a "down to earth" guidance for managers and specialists in organizations who are committed to improving their safety, health, and environmental performance, but are not sure where to start or do not wish to employ consultants to do this for them, They do it themselves using this book."--Resumé vydavatel
Keywords: environmentální audit; hygiena práce; bezpečnost práce; bezpečnostní management; environmental auditing; industrial hygiene; occupational safety; safety management; elektronické knihy; příručky; electronic books; handbooks and manuals